Frank H. Knight in Iowa City, 1919-1928 - Emmett, Ross B.; Biddle, Jeff. (Bingley, U.K. : Emerald, 2011)
The collection includes both refereed articles and review essays. The articles highlight research on the role of western economic advisors in China before the Communist Revolution (Paul Trescott), John Ryan on minimum wage legislation, a symposium on Clement Juglar, and a comparison of recent work in the history of economics and the history of science. Review essays on new publications examine a range of subjects, including: David Humes political economy; conceptions of economic morality in American thought; Frank Knight and the Austrians on institutions; Friedrich Engels; Austrian views on entrepreneurship; Coase and Pigou on government intervention; Hayek and conservatism; the history of the'living wage' notion; methodological consideration of economics and econometrics; and Paul Heynes essays on economic and ethics.
Frank Hyneman Knight : the Iowa years / Gerald L. Nordquist, Ross B. Emmett -- A conversation with Ethel Verry Knight / Gerald L. Nordquist -- The problem of value in economic theory / Ross B. Emmett -- Economics and business / Ross B. Emmett -- The tariff / Ross B. Emmett -- Business management : science or art? / Ross B. Emmett -- A'scientific' observation regarding socialism / Ross B. Emmett -- In defence of agricultural relief on the general plan of the McNary-Haugen measure / Ross B. Emmett -- Social organization : a survey of its problems and forms from the standpoint of the present crisis / Ross B. Emmett -- The mathematical method in treating the price problem / Ross B. Emmett -- Logical method in the social sciences / Ross B. Emmett -- The'concept' of spirituality / Ross B. Emmett -- On power : the invincible logic of asceticism / Ross B. Emmett -- Love and force / Ross B. Emmett -- The ethics of the state / Ross B. Emmett -- Dismal science / Ross B. Emmett -- Non-economistic value / Ross B. Emmett -- Play, art, and work : a little book on the value problem for students of the social sciences / Ross B. Emmett -- The relation of ethics and economics / Ross B. Emmett -- The conflict between the religious and the scientific attitude towards life / Ross B. Emmett -- Liberalism and religion, II : the content of liberal religion / Ross B. Emmett -- Society : freshman lecture / Ross B. Emmett -- Some explorations in the twilight zone between economics and ethics / Ross B. Emmett -- Science and human values : summary, partly as it was and partly as it should have been! / Ross B. Emmett -- On force : B-H group / Ross B. Emmett -- Some observations on the why of human behavior / Ross B. Emmett -- Types of personal relations : on personal and impersonal association / Ross B. Emmett -- Science and efficiency in physics and politics / Ross B. Emmett -- Memorandum to President Jessup on Meredith Plan for Farm Relief / Ross B. Emmett -- Some misconceptions in regard to federal taxation / Ross B. Emmett -- Efficiency and the social ideal / Ross B. Emmett -- The professor and farm relief / Ross B. Emmett -- Discussion group on religion / Ross B. Emmett -- Being and doing / Ross B. Emmett -- Presuppositions of competition / Ross B. Emmett -- Jottings on value : October 8, 1925 / Ross B. Emmett -- What we want : an attempt to list primary wishes or elements in motivation / Ross B. Emmett -- Some notes on value / Ross B. Emmett -- Jottings on value : April 10, 1926 / Ross B. Emmett -- Notes on motivation : second installment / Ross B. Emmett -- Reason, or rationality, and behavior, or value! / Ross B. Emmett -- Notes on human nature and value / Ross B. Emmett -- Note in discussion of personality / Ross B. Emmett -- The issues in value theory / Ross B. Emmett -- Economics and ethics : course outline and reading list / Ross B. Emmett -- Notes on industrial evolution : to accompany Ely, outlines of economics / Ross B. Emmett -- Outline and summary of price theory : to supplement and amend Ely, outlines of economics / Ross B. Emmett -- Energy, human energy, and value : review of the economy of human energy / Ross B. Emmett -- Review of common wealth / Ross B. Emmett -- Economic theory restated / Ross B. Emmett.
Keywords: Economics